Comprehensive simulation of nitrate transport in coupled surface-subsurface hydrologic systems using the linked SWAT-MODFLOW-RT3D model. (December 2019) - Wei, Xiaolu; Bailey, Ryan T.; Records, Rosemary M.; Wible, Tyler C.; Arabi, Mazdak
Abstract: This paper presents SWAT-MODFLOW-RT3D, a model that couples the semi-distributed watershed model SWAT (Soil and Water Assessment Tool) with the groundwater flow model MODFLOW and the groundwater solute reactive transport model RT3D to simulate nitrate (NO3 ) fate and transport in a watershed system. The model is based on a recently developed SWAT-MODFLOW model, with RT3D now called as a subroutine within the MODFLOW code to provide a single, stand-alone model code. RT3D uses NO3 concentration of deep percolation water from SWAT and groundwater heads and flows from MODFLOW to simulate spatially-varying groundwater NO3 concentration and NO3 loading to/from streams, with the latter used by SWAT to route NO3 mass through the network. Model use is demonstrated through an application to the Sprague River Watershed (4100 km 2 ) in Oregon. Other chemical species of interest can be included in the RT3D reaction module in applications of the model to other watersheds. Highlights: SWAT, MODFLOW, and RT3D models are coupled for watershed NO3 transport. Internal mapping is used to pass data between SWAT, MODFLOW, and RT3D. MODFLOW is called as subroutine with SWAT; RT3D as subroutine with MODFLOW. Coupled model is a single FORTRAN code and executable. Modelling framework is applied to Sprague River watershed in Oregon.